A corpus-driven study on legal translation challenges among Arab law students: examining gender and academic level in applied legal linguistics - Dalia M. Hamed; Naif Alqurashi (Humanities & Social Sciences Communications)
Abstract This study introduces Applied Legal Linguistics (ALL) as a praxis-oriented framework that integrates linguistic theory, corpus-based analysis, and legal discourse studies to address the pedagogical, translational, and communicative challenges of legal language use in multilingual and cross-systemic legal contexts. Within this framework, the inquiry investigates the challenges encountered by Arab law students in the English section of the Faculty of Law as they translate legal texts between structurally and culturally divergent legal systems. Anchored in the framework of SDG-4, which advocates for the provision of quality education, this research specifically explores the influences of gender and academic level on the students’ translation competencies. A sample of 139 students, stratified by gender (Male Legal English Section Students (MLESSs), Female Legal English Section Students (FLESSs)), and academic level (2nd-year Legal English Section Students (2nd LESSs), and 4th-year Legal English Section Students (4th LESSs)), participated in the study. The participants translated a legal text, and their outputs were compared to a reference translation produced by two expert legal translators. Utilizing a multidimensional error analysis model assessing lexical, syntactic, spelling, punctuation, and stylistic features, this corpus-driven analysis evaluated various dimensions of the students’ translations. A qualitative examination was conducted to identify error distributions and to assess the degree to which gender and academic level influence the translational outcomes. The findings indicate that 2nd-year students made more frequent lexical, grammatical, and punctuation errors than their 4th-year counterparts, while male students exhibited higher error rates overall than female students, particularly in lexical and grammatical categories. The investigation recommends structured workshops and targeted training, especially for male and early-stage students. It contributes to legal translation research by addressing the overlooked influence of gender and academic level, and by revealing how language proficiency and legalese complexity interact within the context of Arab legal education.